Documenting and analyzing pre-reflective self-consciousness underlying ongoing performance optimization in elite athletes: the theoretical and methodological approach of the course-of-experience framework - Terrien, Eric; Huet, Benoît; Iachkine, Paul; Saury, Jacques (Frontiers in Psychology, 2024)
Traditional theories of motor learning emphasize the automaticity of skillful actions. However, recent research has emphasized the role of pre-reflective self-consciousness accompanying skillful action execution. In the present paper, we present the course-of-experience framework as a means of studying elite athletes’ pre-reflective self-consciousness in the unfolding activity of performance optimization. We carried out a synthetic presentation of the ontological and epistemological foundation of this framework. Then we illustrated the methodology by an in-depth analysis of two elite windsurfers’ courses of experience. The analysis of global and local characteristics of the riders’ courses of experience reveal (a) the meaningful activities accompanying the experience of ongoing performance optimization; (b) the multidimensionality of attentional foci and the normativity of performance self-assessment; and (c) a micro-scale phenomenological description of continuous improvement. These results highlight the fruitfulness of the course-of-experience framework to describe the experience of being absorbed in an activity of performance optimization.